The role of innovation in increasing the competitiveness of the economy of Ukraine - Ivanova, T. (Ways to Improve Construction Efficiency, 2022)
The main source of the country's economic development in modern conditions is innovation, which is the key component of effective changes in the activities of both individual enterprises and the country as a whole. The analysis of existing approaches to the definition of innovations and innovative development shows insufficient practical training and the spread of entrepreneurial and innovative culture among the population of Ukraine, which is based on intellectual capital. The purpose of the study is to substantiate the essence and role of innovations in the process of stimulating innovative development as a factor in increasing the competitiveness of the domestic economy. The article examines existing approaches to defining the concept of "innovation" and their defining components. The classification of innovations, their essence, and the necessity of their functioning in unity was emphasized. The essence of innovative development and its basis, which includes a combination of intellectual capital, investments and a specific innovative and entrepreneurial culture, are revealed. In the conditions of the innovative development of the economy in order to increase its competitiveness, an important place among the priorities at the macro and micro levels is occupied by innovations, the creation and implementation of which is facilitated by the effective use of the intellectual and innovative potential of the country. This creation of an innovative economy is facilitated by the symbiosis of entrepreneurship, the state and education. It is education that needs to be given significant attention in order to develop the abilities, intellectual potential of the population of Ukraine, a creative approach to solving practical situations, and establishing an entrepreneurial and innovative culture in society. The main obstacles to the development of the innovative economy are identified and ways to solve the identified problems that arise and require solutions both at the level of the state and at the level of regions, entrepreneurship and the country's population are proposed. The need for a fundamental change in national thinking and a focus on creating innovations in those directions that belong to the agricultural and technological industry, and not on those that have already been developed in other countries, is emphasized. The leading place in the creation and implementation of innovations is occupied by small and medium-sized enterprises, which need state support in the medium and long term. All these measures will help increase the competitiveness of the domestic economy and increase the welfare of the population of Ukraine.